Mechanical behaviour and compatibility analysis of thermoplastic polyurethane polycaprolactone-based new fused deposition modelling filament composite - Raveverma, P.; Ibrahim, M.; Sa'ude, N.; Yarwindran, M. (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), 2018)
The investigation focuses on the development of a Thermoplastic Poly Urethane(TPU), and Polycaprolactone (PCL) based new flexible polymer composite fused deposition modelling (FDM) filament feedstock. In this research study, the mechanical behaviour of the new polymer composite material is fabricated by injection moulding and tested. The mechanical behaviour of injection moulded TPU/PCL composite samples with various blend formulations was investigated experimentally using several mechanical testings. Several combinations of the blend formulations for the new TPU/PCL flexible feedstock was done by volume percentage (vol. %). Based on the experimental data obtained from the mechanical testing done which is the hardness and tensile of the new polymer composite of TPU/PCL has a high potential to be fabricated as the flexible filament feedstock. The blend ratio of 80:20 which as a medium hardness and a higher tensile strength proved to be a highly potential choice to be fabricated as the flexible filament feedstock. The research resulted in the success of extrusion of 1.75 mm of flexible filament for all three ratios of composites and testing it in FDM machine.